PENGARUH PEMBELAJARAN BERBASIS STEM TERHADAP KEMAMPUAN LITERASI PESERTA DIDIK KELAS IX SMPN 2 PULAU PUNJUNG - Restu, Dea Aulia (Jurnal Edukasi dan Penelitian Matematika, 2024)
This study sought to assess the progress of mathematical literacy in grade nine learners at SMPN 2 Pulau Punjung during STEM-based learning. It also sought to investigate how the mathematical literacy of learners engaged in STEM-based learning compares with learners engaged in conventional learning at SMPN 2 Pulau Punjung. The research conducted was descriptive and quasi-experimental, using a posttest-only non-equivalent control group design. The sampling technique utilized simple random sampling. This study used quizzes and the final assessment of mathematical literacy as instruments. Analysis of quiz data showed an increase in the mathematical literacy of students involved in STEM-based learning. Hypothesis testing has shown the impact of STEM learning on students' mathematical literacy.Keywords– Mathematical Communication Skills, STEM Based Learning, Direct Learning